Le pool de responsabilité civile (pollution) du Québec - Ferland, Gaston (Assurances)

(untitled) (HEC Montréal, 1988)
The Pool Responsabilité Civile Pollution – Québec has been formed under the initiative of the Insurance Bureau of Canada – Québec. lt is a voluntary, non-profit, unincorporated association of insurers and reinsurers formed to partially respond to market needs. The Pool is a reinsurance agency that provides market capacity for limited pollution liability insurance to its members, as well as risk evaluation and loss control. The Pool's operations are administered by the Insurers' Advisory Organization Inc. The author is the first President of the Pool. He describes its history and its constitution as given in his speech at a seminar of the Quebec Insurance Institute on 30 November 1987.